Insights into the Regulation of Rhizosphere Bacterial Communities by Application of Bio-organic Fertilizer in Pseudostellaria heterophylla Monoculture Regime - Wu, Linkun; Chen, Jun; Wu, Hongmiao; Qin, Xianjin; Wang, Juanying; Wu, Yanhong; Khan, Muhammad U.; Lin, Sheng; Xiao, Zhigang; Luo, Xiaomian; Zhang, Zhongyi; Lin, Wenxiong (Frontiers in Microbiology, 2016)
The biomass and quality of Pseudostellariae heterophylla suffers a significant decline under monoculture. Since rhizosphere microbiome plays crucial roles in soil health, deep pyrosequencing combined with qPCR was applied to characterize the composition and structure of soil bacterial community under monoculture and different amendments. The results showed compared with the first-year planted (FP), second-year monoculture of P. heterophylla (SP) led to a significant decline in yield and resulted in a significant increase in Fusarium oxysporum but a decline in Burkholderia spp. Bio-organic fertilizer (MT) formulated by combining antagonistic bacteria with organic matter could significantly promote the yield by regulating rhizosphere bacterial community. However, organic fertilizer (MO) without antagonistic bacteria could not suppress Fusarium wilt. Multivariate statistics analysis showed a distinct separation between the healthy samples (FP and MT) and the unhealthy samples (SP and MO), suggesting a strong relationship between soil microbial community and plant performance. Furthermore, we found the application of bio-organic fertilizer MT could significantly increase the bacterial community diversity and restructure microbial community with relatively fewer pathogenic F. oxysporum and more beneficial Burkholderia spp. In conclusion, the application of novel bio-organic fertilizer could effectively suppress Fusarium wilt by enriching the antagonistic bacteria and enhancing the bacterial diversity.